2021
DOI: 10.1111/jocs.15550
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal cardiopulmonary resuscitation (ECPR) survival: A quaternary center analysis

Abstract: Background: Extracorporeal cardiopulmonary resuscitation (ECPR) has emerged as a rescue strategy for nonresponders to conventional CPR (CCPR) in cardiac arrest.Definitive guidelines for ECPR deployment do not exist. Prior studies suggest that arrest rhythm and cardiac origin of arrest may be variables used to assess candidacy for ECPR.Aim: To describe a single-center experience with ECPR and to assess associations between survival and physician-adjudicated origin of arrest and arrest rhythm.Methods: A retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Categories delineating race or ethnicity varied markedly. Overall, 54 studies (58%) found no statistical association between race and/or ethnicity and outcome (37–76), while 36 (39%) observed adverse outcomes in populations from underrepresented/diverse racial or ethnic backgrounds (Black/African American, Asian, Hispanic, or “other”/“non-Caucasian”/“non-White”). Of citations identifying adverse outcomes, 8 (22%) used univariate (77–84) and 28 (78%) used multivariate analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Categories delineating race or ethnicity varied markedly. Overall, 54 studies (58%) found no statistical association between race and/or ethnicity and outcome (37–76), while 36 (39%) observed adverse outcomes in populations from underrepresented/diverse racial or ethnic backgrounds (Black/African American, Asian, Hispanic, or “other”/“non-Caucasian”/“non-White”). Of citations identifying adverse outcomes, 8 (22%) used univariate (77–84) and 28 (78%) used multivariate analyses.…”
Section: Resultsmentioning
confidence: 99%
“… 9–11 The LUCAS is also amenable for use during coronary catheterization 12 , 13 and during Extracorporeal cardiopulmonary resuscitation (ECPR), a rescue strategy for nonresponders to CPR in cardiac arrest. 13 …”
Section: Introductionmentioning
confidence: 99%
“…8 Studies of the Lund University Cardiopulmonary Assist System (LUCAS), a type of MPD with a vacuum head, reported improved perfusion to cerebral neurological systems and coronary arteries, achieving high PCO 2 values compared to standard manual compression. [9][10][11] The LUCAS is also amenable for use during coronary catheterization 12,13 and during Extracorporeal cardiopulmonary resuscitation (ECPR), a rescue strategy for nonresponders to CPR in cardiac arrest. 13 With the expanded distribution of ACD devices, investigations of their relative efficacy and safety in patients with OHCA have increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marinacci et al observed only a 25.5% survival to discharge after ECPR, and that arrest rhythm and etiology seemed to be insufficient predictors of outcome. 25 ECMO is associated with a high rate of neurologic injury, which could be a hemorrhagic stroke or anoxic injury during the cardiac arrest. 26 One way to mitigate the hemorrhagic injury is ideal anticoagulation.…”
mentioning
confidence: 99%